The Relationship Between The Menstrual Cycle and The Incidence of Acne Vulgaris in Female Students at The Faculty of Medicine, Baiturrahmah University Padang Class of 2022 - Sri Handayani; Irma Primawati; Roland Helmizar; Letvi Mona (Sriwijaya Journal of Medicine, 2024)
Acne vulgaris is a disease that attacks the pilosebaceous unit and can cause non-inflammatory and inflammatory lesions, as well as varying degrees of scarring. In Southeast Asia, the prevalence of acne vulgaris reaches 40-80% of cases. The exact etiology and risk factors for the development of acne vulgaris remain uncertain. However, one factor that is thought to play a role is the fluctuation in estrogen and progesterone that occur during the menstrual cycle in women. This study aimed to determine the relationship between the menstrual cycle and the incidence of acne vulgaris in student at the faculty of medicine, Baiturrahmah University, Padang, class of 2022. The type of research is observational analytics, consist of 48 samples using a consecutive sampling technique. Univariate data analysis is presented and bivariate analysis using the chi-square test. Data processing using the computerized SPSS version 25.0. The highest incidence of acne vulgaris was 75.0% and the highest menstrual cycle was normal was 64.6%. There is relationship between menstrual cycle disorders and the incidence of acne vulgaris (p=0.015) and none the relationship between abnormal menstrual cycles and the incidence of acne vulgaris (p=1.000). There is relationship between menstrual cycle disorders and the incidence of acne vulgaris and there is no relationship between abnormal menstrual cycles and the incidence of acne vulgaris instudent at the Faculty of Medicine, Baiturrahmah University, Padang, Class of 2022.